SISTEM DOSING PUMP BERBASIS ARDUINO UNO R3 UNTUK MENAMBAH NUTRISI TANAMAN HIDROPONIK: SISTEM DOSING PUMP BERBASIS ARDUINO UNO R3 UNTUK MENAMBAH NUTRISI TANAMAN HIDROPONIK - Hidayatullah, Muhammad; Khairil; Etiana, Eka; Andriani, Titi; Ali Topan, Paris (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2024)
Currently, many hydroponic plants are still provided with nutrition manually. Therefore, a device was created that is capable of providing nutrition automatically using a dosing pump and Arduino Uno R3. This research aims to find out how to add nutrient solutions automatically. The method used is an experimental method which includes: the tool design stage, testing stage, and data collection stage. To design the tool, all components are assembled into one with Arduino Uno. The results of the dosing pump test with a time variation of 1-30 seconds produced an increasing amount of nutrient solution and the amount of nutrient for each increase in time was around 0.3-0.4 ml. This tool will turn on if the input value is >2.7 and the PWM (Pulse Width Modulation) used is 255. It is hoped that this tool will be useful for the community as a reference when cultivating organic plants in the future.